Design and synthesis of ether derivatives of spliceostatin A and their biological evaluation towards prostate cancer treatment. (12th January 2023) - Hirabayashi, Satoru; Li, Yue; Ohta, Noriko; Ishibashi, Airi; Yoshikawa, Yusuke; Lin, Bangzhong; Fumimoto, Megumi; Takehara, Tsunayoshi; Nunomura, Kazuto; Suzuki, Takeyuki; Haruta, Junichi; Nimura, Keisuke; et al.
Graphical abstract: Abstract: To confirm the hypothesis that the terminal epoxide structure of spliceostatin A may be active through hydrogen bond formation, we designed and synthesized novel ether derivatives of spliceostatin A, whose terminal epoxide is replaced with an ether-based moiety capable of hydrogen bond formation. The results of biological evaluation against AR-V7 and the conformational analysis of each derivative suggest that the terminal epoxide moiety of spliceostatin A expresses its activity through covalent bond formation rather than hydrogen bond formation.